Terahertz Modulation of Even-order Polarization in GaAs - Jianhua Sang; Haoyu Huang; Liwei Song; Ye Tian; Ruxin Li (IEEE Photonics Journal, 2025)
The application of electric fields induces changes in the symmetry of crystals, which can be observed spectroscopically as variations in the even harmonic generation. In this study, we report the ultrafast modulation of GaAs crystal symmetry using strong terahertz field. The modulation is recorded by the vibration of even harmonic intensity which depends on the polarization direction and instantaneous field strength of applied terahertz wave. The interference between intrinsic even-order nonlinearity and terahertz induced polarization is analyzed. This work offers a novel approach to determining key parameters, such as crystal orientation and terahertz field strength.